Steel-concrete composite buildings designing with Eurocodes - Collings, David (Thomas Telford, 2010)
Using the latest methods as outlined in the Eurocodes, and including up-to-date examples of the uses of composite construction in buildings in the UK, US, Asia and other parts of the world, this is a concise and accessible guide to the practical and economical design of composite buildings.